2018
DOI: 10.2147/ott.s159481
|View full text |Cite
|
Sign up to set email alerts
|

Albumin/globulin ratio is negatively correlated with PD-1 and CD25 mRNA levels in breast cancer patients

Abstract: BackgroundPrevious studies have demonstrated the prognostic value of globulin (GLB), albumin (ALB), the ALB/GLB ratio (AGR), body mass index (BMI), hemoglobin (Hb), and prognostic nutritional index (PNI) in breast cancer. The underlying mechanism has been investigated by examining the impact of nutritional parameters on T cells, natural killer cells, and dendritic cells, but little is known about their effect on checkpoint molecules.MethodsHere, we investigated the correlation of mRNA expression of programmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Several recent studies have shown that systemic inflammation plays an important role in tumorigenesis and disease progression, suggesting the potential utility of inflammation as a prognostic marker. 8 , 9 , 16 , 33 35 Tumor-related inflammatory markers include biochemical and hematological indicators such as CA125, and leukocyte, neutrophil, and platelet cell count. Among them, neutrophils promote tumor development by remodeling the extracellular matrix and releasing ROS, nitric oxide, and arginase.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that systemic inflammation plays an important role in tumorigenesis and disease progression, suggesting the potential utility of inflammation as a prognostic marker. 8 , 9 , 16 , 33 35 Tumor-related inflammatory markers include biochemical and hematological indicators such as CA125, and leukocyte, neutrophil, and platelet cell count. Among them, neutrophils promote tumor development by remodeling the extracellular matrix and releasing ROS, nitric oxide, and arginase.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have provided results indicating that AGR may be an independent prognostic indicator in patients with cancer cachexia ( 39 ), and that AGR exhibits prognostic significance in metastatic prostate ( 40 ), rectal ( 41 ), gastric ( 15 ), cervical ( 42 ) and nasopharyngeal cancer ( 43 ). Furthermore, Liu et al ( 44 ) demonstrated that AGR affects the PD-1/PD-L1 pathway in breast cancer, with implications for immunotherapy. Notably, the present study indicated that treatment progression may contribute to a reduction in AGR, and that patients with a high AGR exhibited higher ORR and DCR than those with a low AGR.…”
Section: Discussionmentioning
confidence: 99%
“…The CREAT-X trial's findings demonstrated that adjuvant capecitabine therapy could considerably increase OS and DFS in HER-2-negative breast cancer patients who did not achieve a pCR following NAC, with the TNBC group benefiting the most [7]. The KATHERINE study revealed that the 3-year invasive disease-free survival (iDFS) rate of T-DM1 was considerably higher than that of the trastuzumab group for patients who did not achieve a pCR following 6-8 cycles of neoadjuvant therapy [8]. Although the above drugs have improved the prognosis of breast cancer patients with a nonpCR, it is worth considering screening out patients with poor responses to NAC and the standard adjuvant therapy agents and implementing different treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently examined the relationships among inflammation, nutrition, and malignant tumors [11]. Different inflammatory and nutritional parameters, such as body mass index (BMI), prognostic nutrition index (PNI), albumin to globulin ratio (AGR), neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), monocyte to lymphocyte ratio (MLR), systemic immune-inflammation index (SII), and systemic inflammation response index (SIRI), as well as their combinations, have all been shown to be vital predictors for breast cancer patients [7][8][9][10][12][13][14][15]. However, a single variable can only provide limited information.…”
Section: Introductionmentioning
confidence: 99%